WTO and Nepalese Financial Institutions - Kafle, Narayan Prasad (Banking Journal, 2011)
This article attempts to unveil the possible consequences that have emerged due to Nepal’s accession to the World Trade Organization (WTO) agreements and the preparedness to be demonstrated by the Nepalese financial institutions in reference to their efforts of capacity enhancement so as to set up themselves at par with the international standards. Beginning from the agreed General Agreements on Trade and Services (GATS) provisions on Financial Sector Service (FSS), this paper shall attempt to expose the gap between the expected accommodations and the existing realities. The fundamental assumption manifested through this article is the requirement to perform in urgency so as to take the potential benefits of WTO provisions since there is no way out as Nepal has already signed the agreement. DOI: http://dx.doi.org/10.3126/bj.v1i1.5139 Banking Journal Vol.1(1) 2011: 13-18